2019
DOI: 10.3390/socsci8040115
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Telecoupling and Climate Governance in Jambi Province, Indonesia

Abstract: Current debates on climate change have led to an increased demand for sustainable commodities. Serving this demand, sustainability certification schemes and eco-friendly labels have become prominent mechanisms of climate governance. Smallholder farmers in Jambi province, Indonesia, producing palm oil and rubber as the two dominant smallholder crops, are impacted by this distal demand. Zimmerer et al. (2018) suggest analyzing the potential sustainability in such a context with the multilevel smallholder telecou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Another problem is that the schemes are not yet sufficiently smallholder inclusive (Garrett et al 2016). Smallholders producing under contract with large palm oil companies can be certified more easily, but independent smallholders often lack land titles, information, and training on specific management practices, which are important preconditions for certification (Brandi et al 2015, Kunz et al 2019). These problems can be addressed through improvements in design and implementation.…”
Section: Sustainability Certificationmentioning
confidence: 99%
“…Another problem is that the schemes are not yet sufficiently smallholder inclusive (Garrett et al 2016). Smallholders producing under contract with large palm oil companies can be certified more easily, but independent smallholders often lack land titles, information, and training on specific management practices, which are important preconditions for certification (Brandi et al 2015, Kunz et al 2019). These problems can be addressed through improvements in design and implementation.…”
Section: Sustainability Certificationmentioning
confidence: 99%
“…Despite plantations being certified, there was no evidence to support sustainability in biodiversity conservation and the reduction of fires [39,41]. A study in Jambi, Indonesia showed that the requirement of good agricultural practices in the RSPO certification does not necessarily influence smallholders to uphold management practices for increased sustainability [42]. However, based on research in Colombia, evidence of enhanced environmental practices was found amongst certified producers at the farm level, including the substitution of synthetic fertilizers with organic.…”
Section: Environmental and Biodiversity Preservation Componentmentioning
confidence: 99%
“…From a social perspective, the adoption and impact of certification on smallholders from various aspects including livelihood, management, compliance with certification and agricultural practices, has been widely explored [32,41,42,[45][46][47]. The impact of the RSPO on smallholders has been studied by Hutabarat et al, [32], Brandi et al [45], Hidayat et al [48] and Hidayat et al [49].…”
Section: Socio-economic Componentmentioning
confidence: 99%
“…The province hosts two privately managed ERCs and three REDD+ projects involving NGOs (Hein, 2019). The RSPO has certified companies and smallholders managing oil palm plantations in the province (Brandi et al, 2015;Kunz et al, 2019). However, recent studies indicate that sustainability certification has not led to significant changes in land management (Kunz et al, 2019) and the privately managed ecosystem restoration initiatives and REDD+ projects are highly contested (Hein, Adiwibowo, Dittrich, Soetarto, & Faust, 2016;Hein, Faust, Kunz, & Mardiana, 2018;Kunz, Hein, Mardiana, & Faust, 2016).…”
Section: Privatized Conservation Land Use and Conflict In Jambimentioning
confidence: 99%